Understanding Gen Z Tour Guides : Key Factors Affecting the Attraction and Retention in Ho Chi Minh city - Han, Gia Yen; Hořáková, Marie; Legnerová, Kateřina, 1965-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
Ho Chi Minh City is one of the key tourist centers in Vietnam and attracts an abundance of both domestic and international tourists. However, the city is currently facing a shortage of tour guides, especially young professionals who are skilled and passionate. As Generation Z gradually takes up a large number in the workforce in the tourism industry, attracting and retaining young tour guides has become one of the major challenges for tourism businesses. The thesis was conducted based on quantitative approach, with an aim to analyze the factors that influence the intention to stay long-term of Gen Z tour guides in Ho Chi Minh City. A total of 203 responses were collected via online surveys and 196 were valid, then incorporated into SPSS 30.0 for Cronbach’s Alpha reliability testing, Exploratory Factor Analyis (EFA) and regression analysis. The research findings revealed that career advancement opportunities, work-life balance, competitive compensation and benefits have a positive influence on the intention to stay long-term of Gen Z tour guides with tourism businesses in Ho Chi Minh city, in which, Career Advancement Opportunities was found to have the strongest influence. Based on the research findings, solutions were proposed by the author to help tourism companies in Ho Chi Minh city improve their strategies for attracting and retaining talented Gen Z tour guides and enhance their competitiveness in the industry.
Vedoucí práce: Marie Hořáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses